Employee Engagement: Analysis of The Motivation to Stay or Leave The IT Directorate Of Bank Tangguh - Pardede, Lia Martina; Bangun, Madju Yuni Ros (SBM ITB, 2021)
Abstract. The aim of this study is to identify the factors of employee engagement which influence employees' motivation to stay or leave and to develop a retention strategy for IT employees in Bank Tangguh. After merging with its shareholder, Bank Tangguh has the eighth largest assets in the banking industry in Indonesia. This has enhanced the company's reputation and brand. However, a high rate of IT turnover is still a big challenge for Bank Tangguh Data for this issue are collected using questionnaires and interviews. This study uses the employee engagement model of Fajar & Bangun (2017) and the happiness drivers identified by Hills and Argyle (2002). The employee engagement factors are company brand, leadership, performance, the basics, post-merger drivers, happiness drivers. They are mapped against the engagement behaviors (say, stay, and strive). A normality test and reliability and validity tests are performed to ensure the proper instruments are being used. The results showed that there are three main reasons for employees to stay—performance, post-merger drivers, and the basic—and three main reasons to leave: the basic, performance, and leadership. Based on those findings, the author proposes a strategy to retentain IT employees in Bank Tangguh to reduce the turnover rate.Keywords: Employee engagement, retention, turnover, motivation, banking industryAbstrak. Tujuan dari penelitian ini adalah untuk mengidentifikasi faktor-faktor keterlibatan karyawan yang mempengaruhi motivasi karyawan untuk tinggal atau pergi dan untuk mengembangkan strategi retensi bagi karyawan IT di Bank Tangguh. Setelah bergabung dengan pemegang sahamnya, Bank Tangguh memiliki aset terbesar kedelapan di industri perbankan di Indonesia. Ini telah meningkatkan reputasi dan merek perusahaan. Namun, tingkat perputaran IT yang tinggi masih menjadi tantangan besar bagi Bank Tangguh. Data pada studi ini didapat melalui kuesioner dan wawancara. Studi ini menggunakan model keterlibatan karyawan Fajar & Bangun (2017) dan happiness drivers yang diidentifikasi oleh Hills and Argyle (2002). Faktor keterlibatan karyawan adalah merek perusahaan, kepemimpinan, kinerja, the basics, post-merger drivers, happiness drivers. Hal tersebut dipetakan terhadap perilaku keterlibatan (berpendapat, menetap, dan meninggalkan). Tes normalitas dan uji reliabilitas serta validitas dilakukan untuk memastikan instrumen yang tepat digunakan. Hasilnya menunjukkan bahwa ada tiga alasan utama bagi karyawan untuk menetap - kinerja, post-merger drivers, dan the basics - dan tiga alasan utama untuk meninggalkan: the basics, kinerja, dan kepemimpinan. Berdasarkan temuan tersebut, penulis mengusulkan strategi untuk kembali mempertahankan karyawan IT di Bank Tangguh untuk mengurangi tingkat turnover.Kata kunci: Keterlibatan karyawan, retensi, perputaran, motivasi, industri perbankan